Conference Report: 6th GCC focus on LBA: critical reagents, positive controls and reference standards; specificity for endogenous compounds; biomarkers; biosimilars. (October 2012) - Nicholson, Robert; Lowes, Steve; Caturla, Maria Cruz; Safavi, Afshin; Mamelak, Dan; Islam, Rafiq; Allinson, John; Gouty, Dominique; Khan, Masood; LeLacheur, Richard; Shoup, Ronald; Martinez, Suzanne; et al.
The 6th Global CRO Council for Bioanalysis (GCC) Closed Forum was held on 27 March 2012 in San Antonio, TX, USA, the day before the start of the 6th Workshop on Recent Issues in Bioanalysis. The attendance consisted of 45 bioanalytical CRO senior-level representatives on behalf of 37 CRO companies/sites from six countries. In addition to following up on the issue of co-administered drugs stability and on recommendations regarding the European Medicines Agency guideline, this GCC Closed Forum discussed topics of current interest in the bioanalytical field with focus on ligand-binding assays, such as lot changes for critical reagents, positive controls and reference standards, specificity for endogenous compounds, qualification and validation of biomarker assays, approach for biosimilars and criteria for LC–MS assays of small versus large molecules.